Review of IIMI's experience in strengthening national capacity for irrigation management and research. Parts 1 and II - Rao, P.S.; Abeywickrema, N. (International Irrigation Management Institute, 1992)
Over the past few years IIMI has acquired a rich and rewarding storehouse of experience in its relations with national partners and collaborating agencies, some of which are unique and innovative. The Management Committee therefore decided that IIMI collects and documents this experience for future reference and consideration by senior management, and the Board of Governors. As the first phase in this effort, Regional Representative West Africa, and all Heads of Field Operations and Project Leaders were asked to list and inventorise their experience with national partners and other collaborating agencies in their work operations. This included both formal, official as well as informal relationships which contributed to strengthen better understanding and impact on national programs. Known activities were to be listed with some degree of description, whereas additional information was to be provided on lesser known and informal activities. The report of these experiences was presented initially to the Management Committee Meeting of February 1992. In February 1992, the Management Committee decided that based on past experience, a more comprehensive document which recognized the need to generate a conceptual framework to strengthen national capacities, be developed. This set in motion a second phase of work. In March 1992, Director Pakistan, Regional Representative West Africa, Heads of Field Operations (present and former) and Project Leaders in Field Operations were requested to provide an internal review of achievements to date and recommendations in their efforts at strengthening national capacities. Specific examples of country experience, assessment of the circumstances that made it possible, and the environment that fostered close relationships facilitating the strengthening of national capacity were to be provided.